Studi Komparatif: Kualitas Layanan Mobile Banking BRI Syariah dan Bank Syariah Indonesia - Muhammad Zulvan Jamalu Ramadhan; Vemy Suci Asih (Indonesian Journal of Economics and Management, 2021)
The purpose of this study is to show whether or not there is a difference in the quality of the value of mobile banking at BRI Syariah and Bank Syariah Indonesia. In this study, quantitative techniques were used by straddling a sample of 35 respondents where customers of Bank Syariah Indonesia (BSI) Ex. Bank Rakyat Indonesia Syariah (BRIS) KCP Sumedang Tanjungsari 2 which responded to the quality of mobile banking services between before and after becoming Bank Syariah Indonesia (BSI). The indicator of the quality of the mobile banking service used is a questionnaire or questionnaire distributed in this study, while checking the hypothesis using a free sample t test. Judging from the results of analyzing the data, it can be seen the average value of mobile banking services at Bank Syariah Indonesia > the average value of mobile banking services at BRI Syariah. It can be concluded that the quality of mobile banking services felt by customers at Bank Syariah Indonesia is better than BRI Syariah, while judging by the results of the free sample t-test data, this study did not get a significant difference between mobile banking services at BRI Syariah and Islamic Banks. Indonesia.